PEMANTAUAN PELAKSANAN SELEKSI KOMPETENSI DASAR (SKD) CALON PEGAWAI NEGERI SIPIL TAHUN 2019 Studi Pada Badan Kepegawaian Pendidikan dan Pelatihan Kota Magelang Tahun 2020 - Sukoariyah Sri Puji Astuti (Badan Perencanaan Pembangunan Daerah Kota Magelang, 2021)
This study aims to analyze the implementation of Basic Competency Selection (SKD) in the recruitment of Prospective Civil Servants (CPNS) in 2019 with the Computer Assisted Test (CAT) system in the Magelang City Civil Service Education and Training Agency in 2020. This study is included in the type of qualitative research with descriptive methods in which descriptive research describes the object under study based on existing facts. Data sources from this research are primary data and secondary data. The results showed that the implementation of the Basic Competency Selection (SKD) for the Formation of Civil Servants in 2019 at the Magelang City Employment Education and Training Agency in 2020 went smoothly in accordance with the provisions.